Clinical Issues‐September 2015. (30th August 2015) - Van Wicklin, Sharon A.; Brubaker, Scott A.
This Month: Surgical wound classification Key words: wound classification, documentation, surgical site infection. Storing and using small, prefilled containers of formalin in the OR Key words: formalin, formaldehyde, eyewash stations, Occupational Safety and Health Administration. Latex‐free environments for tissue recovery and organ procurement procedures Key words: allografts, organ donation, tissue recovery, latex sensitivity, latex‐free environment. Covering facial hair in semirestricted and restricted areas Key words: facial hair, beards, surgical masks. Covering ears in semirestricted and restricted areas Key words: ears, pierced earrings, surgical head coverings.